2001
DOI: 10.1046/j.0960-7439.2001.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the palate dimensions of patients with perennial allergic rhinitis

Abstract: The transverse dimension of the palate did not vary significantly between the groups, which seems to confirm that the main influence of alteration of the breathing pattern from nasal to mouth occurs on the vertical plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
19

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 13 publications
(23 reference statements)
4
35
0
19
Order By: Relevance
“…These results are in agreement with studies involving children with and without allergic rhinitis of Freitas et al [23] and Ghasempour et al [24] who observed that the palatal height was significantly greater in children with allergic rhinitis than in nasal-breathing group. In contrast Vieira et al [3] investigated white preschool individuals and found that mouth-breathing had no impact on palatal height.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with studies involving children with and without allergic rhinitis of Freitas et al [23] and Ghasempour et al [24] who observed that the palatal height was significantly greater in children with allergic rhinitis than in nasal-breathing group. In contrast Vieira et al [3] investigated white preschool individuals and found that mouth-breathing had no impact on palatal height.…”
Section: Discussionsupporting
confidence: 93%
“…As in our study, in another previous study, 28 it has also been observed that they have shorter maxillary and mandibular lengths. The pharynx was evaluated at five different vertical points, with the purpose of evaluating if there were any specific areas of bigger or smaller dimension.…”
Section: 21supporting
confidence: 75%
“…Mouth breathers presents: bigger facial height, [24][25][26] higher frequency of maxillary retrognathism, [25][26][27] 29,30 normal upper inter-molar and inter-canine distance, 28 decreased perimeter of superior and inferior arch, 29,31 vestibular tilting of the upper incisors, 21 retro-inclination of inferior incisors, 21,26 and greater dental crowding.…”
mentioning
confidence: 99%
“…These findings underline the applicability of these tests in a clinical setting, as confirmed in the literature. 14,15 A specific analysis was made of the nasal block score, because this symptom predominates in allergic rhinitis [14][15][16][17][18] and it relates directly with the presence of dysfunctions in the stomatognathic system 4,6,8,9,11,12,21,22 . Table 5 shows the comparison of this symptom in both groups, which revealed a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%